Using Inquiry learning Method and Ladder Snake Game to Teach Reading Skills for The 7th Grade Students of SMPN 1 Kartoharjo - Muhammad Azka Fahmi; Sumani Sumani; Fitra Pinandhita (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
: This research explores the implementation of "Ladder Snake" game and the inquiry learning method to teach reading skills 7th-grade students. The study aims to address the challenges students face in understanding sentences and words. By using game-based learning and inquiry-based teaching, the research seeks to increase student engagement and motivation while promoting critical thinking. The study employs qualitative research methods, including observation, interviews, document analysis, to gather data. The findings reveal the benefits and limitations of using "Ladder Snake" game and inquiry learning method in the classroom. The research highlights the importance of reading as a fundamental skill for understanding different perspectives and acquiring vocabulary. It suggests that the integration of interactive games and student-centered learning approaches enhance students' reading abilities and their text comprehension. The results show that the game-based approach improves student interest and comprehension, but some students struggle with quick translation and vocabulary building. To address these challenges, the study proposes strategies such as word association exercises and continuous vocabulary expansion. Overall, this research provides insights into the effective use of the "Ladder Snake" game and inquiry learning method for teaching reading skills. By implementing these approaches, educators can enhance students' reading comprehension and language learning outcomes.